Supporters’ Chant Support and Senior Football Athletes’ Self-Confidence During Competitions - Muhamad Rizky Al Mustopa; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Salma Maharani Sopandi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Supporter chant support is one of the external factors that can influence an athlete's mental state, especially in soccer (Abdullah et al., 2016). Chant provided during a match can create an atmosphere that influences an athlete's level of self-confidence. This study aims to determine the role of supporter chant support on the self-confidence of senior soccer athletes during matches. The method used in this study is descriptive with a quantitative approach, involving 23 soccer athletes competing in the Indonesian professional league. The instrument used for data collection was a Likert scale questionnaire, consisting of 71 questions to measure the level of supporter chant support and self-confidence indicators administered once to the sample. After the data was obtained, the data were analyzed using the SPSS 25 correlation test. The results showed a significant relationship between supporter chant support and soccer athletes during matches. This study concluded that supporter chants play an important role in increasing soccer athletes' self-confidence, thus supporting their performance to improve externally. Therefore, the researcher recommends that supporters continue to provide positive support through positive chants to build an athlete's self-confidence during matches.